2022
DOI: 10.1101/2022.03.18.484947
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Mitochondrial Matrix Protease ClpP Agonists inhibit Cancer Stem Cell Function in Breast Cancer Cells by Disrupting Mitochondrial Homeostasis

Abstract: Mitochondria are multifaceted organelles which are important for bioenergetics, biosynthesis and signaling in metazoans. Mitochondrial functions are frequently altered in cancer to promote both the energy and the necessary metabolic intermediates for biosynthesis required for tumor growth. Cancer stem cells (CSCs) contribute to chemotherapy resistance, relapse, and metastasis. Recent studies have shown that while non-stem, bulk cancer cells utilize glycolysis, breast CSCs are more dependent on oxidative phosph… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 73 publications
0
2
0
Order By: Relevance
“…Whether this effect is parallel to the reactivation of cancer stem-like cells has to be shown. A paper recently showed that knock down of PYCR1 and 2 effectively blocked the formation of mammospheres (12) in contradistinction to inhibitors of glutaminase which had little effect on mammosphere formation. This finding clearly defines that although glutamine serves as the main delivery source of degradation products of various amino acids and proteins, it is the synthesis of proline which is critical for forming mammospheres, an accepted criteria of renewal of cancer stem-like cells (24).…”
Section: Proline Metabolism Mediates Transitional Pluripotencymentioning
confidence: 99%
See 1 more Smart Citation
“…Whether this effect is parallel to the reactivation of cancer stem-like cells has to be shown. A paper recently showed that knock down of PYCR1 and 2 effectively blocked the formation of mammospheres (12) in contradistinction to inhibitors of glutaminase which had little effect on mammosphere formation. This finding clearly defines that although glutamine serves as the main delivery source of degradation products of various amino acids and proteins, it is the synthesis of proline which is critical for forming mammospheres, an accepted criteria of renewal of cancer stem-like cells (24).…”
Section: Proline Metabolism Mediates Transitional Pluripotencymentioning
confidence: 99%
“…Although it would take a voluminous review to cover them all, I have taken the liberty of emphasizing a number of new and somewhat unexpected discoveries. These include: 1) The transitional pluripotency mediated by proline metabolism in embryonic stem cells (ESC) (11), and 2) also in cancer stemlike cells (CSC) (12); 3) The interaction between proline metabolism and hydroxyproline metabolism (13) 4) the effect of hydroxyproline with HIF-1a (13); 5) the hydroxylation of collagen and its modulation of demethylation in TET and Jmj (8); 6) In CAR-T Lymphocytes, screened by gain-of-function CRISPR screens, the discovery that PRODH2 (hydroxyproline dehydrogenase) was the only gene which significantly activated the tumorlytic effect of CAR-T cells (14). We will discuss these subjects in order and attempt to explain the mechanisms and their implications using state-of-the-art insights into proline metabolism and cancer (11).…”
Section: Introductionmentioning
confidence: 99%